Mortality of Betle Callosobruchus Chinensis Due To Provision of Clove Powder (Syzygium Aromaticum) - John Alfred Patty; Ria Yeane Rumthe (Faculty of Agriculture, Pattimura University, 2020)
The development of plant-based pesticides has become an effective way to suppress pest populations. The application of clove handle powder to population growth (Callosobruchus chinensis L) is important to be studied, because it is a less biodegradable pesticide with fewer residu and safer for humans and livestock. The objective of this study was to obtain an effective dose of clove (Syzygium aromaticum) powder for controlling beetles (Callosobruchus chinensis L.) in stored mung bean. The study method was a Completely Randomized Design with 5 treatments of clove handle powder doses, namely control, 10 g, 15 g, 20 g, 25 g. The results showed 70% or the highest mortality rate of C. chinensis L. is found at a dose of the 25 g, with the fastest average time of death is 16 JSA, while the lowest dose of 10 g indicates 56,67% of the the mortality rate of C. chinensis L with 24 JSA time after application.